The analysis of acculturation stress and strategies for coping with stress among English Program students of the Pomeranian Medical University in Szczecin - Szkup, Małgorzata; Polakiewicz, Paulina; Schneider-Matyka, Daria; Jurczak, Anna; Stanisławska, Marzanna; Wieder-Huszla, Sylwia; Kotwas, Artur; Karakiewicz, Anna; Grochans, Elżbieta (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Nowadays we can observe an increase in educational migration. International students staying in a foreign country are in the process of acculturation. This process is individual and dependent on many factors. Aim. The aim of this study was to analyze acculturative stress experienced by Scandinavian students of the Pomeranian Medical University in Szczecin, Poland. Variables taken into consideration were: perceived discrimination, homesickness, fear, perceived hate, culture shock, guilt, and other non-specific factors. Material and methods. This survey-based study was conducted between 2011–2012. It involved 129 medical students from the Scandinavian countries, including 77 women and 52 men. The average age of respondents was 22.66 years. Acculturative stress was assessed with the Acculturative Stress Scale for International Students (ASSIS) developed by D.S. Sadhu and B.R. Asrabadi. Stress-coping strategies were analyzed with Carver’s Brief Cope Scale. Participation in the survey was anonymous and voluntary. A statistical analysis was performed using the Pearson product-moment correlation coefficient and the Spearman’s range correlation coefficient. Results. Based on the results, the average level of acculturative stress was established (79.15 points). The worst aspects of acculturative stress in respondents’ opinions were: homesickness, culture shock, and other nonspecific factors (e.g. problems with communication, social isolation, threats to cultural identity, lower social status than in the country of origin). Conclusions. 1. Studying in a foreign country entails acculturative stress. Scandinavian students in Poland are doing quite well. They mainly complain about homesickness. 2. Integration programs implemented by host countries can be a significant support for foreign students. Nursing Topics 2014; 22 (1): 74–81